Genome size determination of Ficus deltoidea using flow cytometry method - Zailani, Siti Sarah; Fikri, Muhammad Irfan; Midin, Mohd Razik (Noor Publishing, 2021)
Ficus deltoidea is a large shrub native to Southeast Asia. locally, it is known as 'Mas cotek'. It is famous for its medicinal value and health benefits. As for now, genome size data of F. deltoidea is not available yet. This study aims to optimise nuclei preparation method of flow cytometry (FCM) measurement as well as determine the nuclear genome size of F. deltoidea. Several steps involved in this study: (1) isolation of nuclei using two different techniques (manual chopping and Medi-machine) and two different lysis buffers (Otto and LBO1), (2) nuclear DNA staining using propidium iodide (PI) dye and (3) measurement of fluorescent intensity of stained nuclei. DNA histograms generated from different methods and lysis buffers were compared. This study revealed that the best DNA histogram was obtained by using manual chopping technique supplemented with Otto buffer. Using FCM with Glycine max cv. Polanka (2C=2.5pg) as an external reference standard, the genome size of F. deltoidea was found to be 2.88 pg. The genome size data can be utilised in future studies of ecology, evolution, taxonomy as well as genome sequencing.